The Deep Focus Typecasting of Joseph Schildkraut as Judas Figure in Four DeMille Films - Kozlovic, Anton Karl (Journal of religion and popular culture, 2004)
Cecil B. DeMille is an unsung auteur director, a master of the American biblical epic, and a founding figure of Hollywood. However, critics have routinely dismissed him as unfashionable, inauthentic or disingenuous. Rarely have DeMille's credentials as a legitimate religious artist been seriously investigated, acknowledged or applauded. One of his cinematic trade secrets was the utilisation of deep focus casting, that is, the engineering of significant correspondences between his on-screen characters and his actors' personal idiosyncrasies, which eventually resulted in their typecasting. Using humanist film criticism as the analytical lens, the critical literature is reviewed and eight components of DeMille's deep focus casting philosophy are identified. This understanding is then applied to Joseph Schildkraut and his Judasean betrayer roles within The King of Kings, Cleopatra, The Crusades and The Road to Yesterday. It is concluded that Schildkraut was typecast as an archetypal betrayer because DeMille needed a good "bad-guy" for dramatic effect and ethnic authenticity, which the Jewish-American actor excelled at performing. The notion that DeMille-the-Christian was fundamentally an anti-Jewish bigot, a rabid racist, or spiteful towards the Schildkraut family is firmly rejected. Further research into DeMille Studies and the pop culture construction of biblical, religious, historical and other screen characters was recommended.